Kratke pripovedi starejše generacije v letih 1925-1929 - Kocijan, Gregor (Slavistična revija, 2010)
The analysis of short fiction in 1025-1926 by the authors born in the 1880's shows that the group in close to the tradition and the short-fiction model of the previous era. The authors attempt to advance their own alternatives witin the existing framework, with an occasional introdution of innovation.
Keywords: 1925/1929; kratka proza; motivi; Slovene literature; slovenska književnost; stilistika; stylistics